Achille Torelli’s Poetry Between ‘Popular Songs’ and Romantic Philhellenism (Altre Modernità, 2025)
The essay aims to trace the presence of elements of the philhellenic literature repertoire that spread during the nineteenth century (not only in the works of authors such as Nievo, Cantù, Tommaseo, and Fauriel), in Achille Torelli’s poetry (1841-1922), playwright, novelist and Neapolitan poet of arbëreshë origin. The research will take into consideration the Albanian popular traditions included in the collection of poems Schegge (1878), reflecting on the double purpose of the rewriting activity: as a contribution to the transmission of that people’s traditions, and also as an exercise in literary erudition. Through the reading of Torelli’s lyrics, the essay aims to document the reworking of the typical elements of the traditional repertoire through the act of rewriting examined in its various forms, using as a case study the verses of a lyric considered ‘the masterpiece’ of Albanian legends, also for its central nucleus, linking it to a vast European tradition that blends popular imagination with the fairy tale: Costanzo’s faith. This legend – placing at the centre the virtue of the knight who does not break his oath even after his death, getting on the back of his horse and accomplishing his task before disappearing definitively from earthly life – is intertwined with the romantic scenario of Bürger’s Lenore and with the Hellenic tradition. In particular, such a tradition is revived both by Fauriel who inserts the lyric under the title Le voyage nocturne in his Chants populaires, and by Tommaseo who brings it back among his Canti Greci titling it The Spectre, up to Torelli’s work who, in presenting as sources the translations of Girolamo de Rada or the anthology of De Grazia, does not hide his work of rewriting full of interconnections between the various literary texts.
Keywords: Achille Torelli, poetry, romantic philhellenism